Design of high-temperature superconducting low-pass filter for broad-band harmonic rejection. - Min Hwan Kwak (IEEE Transactions on applied superconductivity)
A new type of low-pass filter based on a coupled line and transmission line theory is proposed for suppressing harmonics and spurious frequency. The seventh-order coupled-line low-pass filter with strip line configuration was fabricated using a high-temperature superconducting (HTS) thin film on MgO(100) substrate. The seventh-order low-pass filter has five attenuation poles in the stop band. Its cutoff frequency is 1 GHz with a 0.01-dB ripple level. The fabricated filter exhibits a characteristic stop band in the range from 1 to 7 GHz. A measured insertion loss at the pass-band of the HTS low-pass filter is 0.2 dB at 77 K, while the maximum return loss is 17.1 dB. These results match well with those obtained by the EM simulation. The new low-pass filter structure is shown to have attractive properties such as compact size, wide stop band range, and low insertion loss